Spatial diversity of absorption of EU Assistance funds and the level of socio-economic development in Poland - Rudnicki, Roman; Dubownik, Anna; Szyda, Barbara; Adamiak, Czesław (Rozwój Regionalny i Polityka Regionalna, 2019)
The article presents the level and spatial structure of the absorption of EU funds within Cohesion Policy and Common Agricultural Policy during the 2007–2013 EU financial framework in Poland. The data analysed include all of the payments from European programmes, divided into two groups: the support dedicated for the development of agriculture and rural areas, and the cohesion policy. It has been demonstrated that the level and structure of delivery of these funds is spatially diversified. The index of the absorption of EU funds per capita is negatively correlated with the level of socio-economic development, which results from the allocation of payments dedicated for development of agriculture and rural areas. The distribution of cohesion funds is not correlated with the level of socio-economic development in poviats.